Spawning biomass variation in Atlantic Cod (Gadus morhua) in Flemish Cap in Relation to Changes in Growth and Maturation - Saborido-Rey, Francisco; Junquera, Susana (Northwest Atlantic Fisheries Organization, 1999)
Drastic changes in both age- and length-at-maturity of cod (Gadus morhua) on Flemish Cap have been observed during this decade. In the present paper, growth by cohort in this period was analyzed and compared with the observed trend in maturation. Different cohorts displayed different growth rates, the strongest 1990 year-class showing fastest growth. The compensatory response to lower population density alone did not explain the decline in both age- and size-at-maturity. Strong changes in fishing pressure during the period could have provoked a size-selectivity for early maturity, i.e. genetic selection. An estimate of the spawning biomass, accounting for the corresponding size-at-age distributions, on a cohort basis is given. The influence of changes in spawning biomass and spawning stock biomass age structure on the probability of future stock rebuilding is also discussed. It is shown a low spawning biomass composed of young and recruited females will hardly rebuild the stock to historical levels.